Baseline Vitamin B12 and Folate Levels Do Not Predict Improvement in Depression After a Single Infusion of Ketamine - Lundin, N. B.; Niciu, M. J.; Luckenbaugh, D. A.; Ionescu, D. F.; Richards, E. M.; Vande Voort, J. L.; Brutsche, N. E.; Machado-Vieira, R.; Zarate, C. A., Jr (Pharmacopsychiatry, 2014)
Introduction: Deficiencies in both vitamin B12 and folate have been associated with depression. Recently, higher baseline vitamin B12 levels were observed in individuals with bipolar depression who responded to the antidepressant ketamine at 7 days post-infusion. This study sought to replicate this result by correlating peripheral vitamin levels with ketamine’s antidepressant efficacy in bipolar depression and major depressive disorder (MDD).Methods: Baseline vitamin B12 and folate levels were obtained in 49 inpatients with treatment-resistant MDD and 34 inpatients with treatment-resistant bipolar depression currently experiencing a major depressive episode. All subjects received a single intravenous ketamine infusion. Post-hoc Pearson correlations were performed between baseline vitamin B12 and folate levels, as well as antidepressant response assessed by percent change in Hamilton Depression Rating Scale (HDRS) scores from baseline to 230 min, 1 day, and 7 days post-infusion.Results: No significant correlation was observed between baseline vitamin B12 or folate and percent change in HDRS for any of the 3 time points in either MDD or bipolar depression.Discussion: Ketamine’s antidepressant efficacy may occur independently of baseline peripheral vitamin levels.
Keywords: vitamin B12; folate; ketamine; bipolar depression; major depressive disorder